Perhitungan Daya Winch yang digunakan pada Dok Tarik (Launching Way) PT. ASSI - Reydita Safirahaidi; I Putu Sindhu Asmara; Pranowo Sidi (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
PT. Adiluhung Saranasegara Indonesia (PT. ASSI) is one of the companies engaged in the shipping industry. In terms of cost efficiency and field area conditions, the company established 3 types of docking facilities, including Slipway, Launching way, and Floating dock. Every company should have specification data from each facility. But in one of the facilities that are often used in PT. ASSI, launching way, there is a problem with the winch used. The winch doesn't have a complete specification book, so the company doesn't know the power used on the winch. Therefore, in this study presented the calculation of power used in launching way by using ship data that is doing the docking at PT. ASSI. In this calculation, there are several steps, namely the calculation of sling tensile, attractiveness speed, winch pull force, drum, and finally the calculation of torque and power of the electric motor. The result of this study is using 8/1 system pulley, the tensile winch's force is 162,374 k. With the time of docking around 4 hour, the ship's tensile speed is 0,0514 m/s. The result of the power used is 75 kW with a torque of 82810,519 Nm.